Percepção de uma empreendedora manauara sobre a geração de valor em uma loja virtual no Instagram: um estudo de caso na marca Carola's Bracelets - Reis, Josafá Eliel Sousa (Brasil, 2024)
The generation of value in an enterprise is linked to the ability to manage strategies for its development and promotion. The study presented aimed to understand the perception of an entrepreneur from the city of Manaus about generating value for her online store on Instagram. For structuring, a qualitative approach was used, with the adoption of netnographic exploration and semi-structured interviews. Given the results obtained, it was possible to conclude that the entrepreneur from Manaus who works with a venture on the social network Instagram, has solid knowledge about generating value and strategies for promoting her business online, as she uses content creation, delivering value in its products, as well as improving communication with its consumers, always seeking to align the brand's marketing strategies with its brand values, thus aiming to build a community with its followers.